Role of Effective Feed Back in Multiple Choice Questions (MCQs) Designing for Faculty Development - Khalid Farooq Danish , Khalid Farooq Danish; Rehan Ahmad Khan, Rehan Ahmad Khan (Journal of Rawalpindi Medical College, 2010)
errors in multiple choice questions (MCQs) designing by the faculty members and to obtain need assessment feedback for faculty development for MCQ designing. Methods: In this study, all MCQs submitted by faculty members of Islamic International Medical College (IIMC) over a period of one year and three months from January 2009 to April 2010 were reviewed from time to time by the assessment committee. A total of 922 MCQs were reviewed. The reviews were compiled and analyzed to find out the frequency and types of errors made inadvertently in the structure and design of MCQs. Results: During the study period, the faculty members submitted a total of 922 MCQs. Spectrum of errors in MCQs ranged from spellings to complex questions to question cues. A total of 40% items qualified for being included in final assessment Conclusion: Review process is very important in improving the quality of items.